(manuscript) Forest operations and multiple resource management - Dykstra, D.P. (1999)
The contribution of non-timber forest products to the global economy is significant, though probably less than that of timber products. In addition, non-timber resources provide substantial environment benefits that are difficult or impossible to measure in an economic sense but are nevertheless highly valued by society. In all parts of the world and at all levels of economic development, societies increasingly demand that forest managers consider the value of non-timber goods and services in making harvesting and silvicultural decisions. While this is not easy, methodologies are becoming available that at least are beginning to make the task feasible. Technologies that offer promise for incorporating non-timber values into harvesting and silvicultural decisions include the use of comprehensive multiple-resource models to develop plans and to negotiate with interested parties, and the modification of forest practices in an effort to enhance non-timber values through the operations themselves. Operating technologies that reduce damage to residual vegetation, decrease soil disturbance, and improve timber recovery will benefit management while at the same time increasing substantially the value of the non-timber goods and services provided by forests (o)